NOMINALIZATION STRATEGIES OF EXCLUSION REPRESENTED ON THE HEADLINES OF THE JAKARTA POST IN THE CASE OF FEUD OF KPK VS POLRI PART II: A STUDY OF CDA - Muhammad Rayhan Bustam (Balai Bahasa Jawa Barat, 2014)
KPK (Corruption Eradication Commission) and Polri (Indonesian National Police) aretwo agencies that have the authority to handle the corruption perpetrators in Indonesia.The second feud between the two attracts Indonesian people's attention once again.Such widely reported feud caught my interest in analyzing the headlines published onThe Jakarta Post of August to October 2012's editions. The aim of this writing is todiscover the use of nominalization strategies of exclusion in representing the socialactors on The Jakarta Post headlines. The Critical Discourse Analysis method ofTheo van Leeuwen's is used to show how parties and actors (individual or group) arepresented on the news, especially the process of nominalization strategies of exclusion.The results show that the process occurred mostly on Polri. Such exclusion was intendedto focus readers' attention on the other actor (victim), namely KPK.